Depression and pain: some issues of comorbidity and treatment (Review) - Mamchur V.; Khomyak O. (Морфологія, 2011)
The article highlights the current understanding of the mechanisms of pain and depression comorbidity, especially - functioning of neurochemical systems in the brain and the anatomical and functional relationships of structures in the CNS of these pathological conditions. It shows the current classification of antidepressants, analyze the neurochemical aspects of their actions, effects on cognitive brain function and behavioral reactions to the formation of the sensations of pain, generalize mechanisms of action in the treatment of chronic pain. In the analysis of the literature it is concluded that depres-sion and pain therapy impede each other, having common mechanisms of development, the leading points of contact they are changing the functioning of catecholaminergic neurotransmitter systems of the brain, the levels of certain cytokines, as well as the state of NMDA-dependent mechanisms of the brain. The question of their use for treatment of acute pain, includ-ing differentiated into non-opioid analgesics combined with, is not sufficiently understood.